The history of live music in Britain, Volume 2, 1968-1984, From Hype Park to the Hacienda - Frith, Simon 1946- (Ashgate popular and folk music series, 2019)
To date, there has been a significant gap in work on the social history of music in Britain from 1950 to the present day. The three volumes of Live Music in Britain address this gap and do so through a unique prism--that of live music. The key theme of the books is the changing nature of the live music industry in the UK, focused upon popular music but including all musical genres. Via this focus, the books offer new insights into a number of other areas, including the relationship between commercial and public funding of music, changing musical fashions and tastes, the impact of changing technologies, the changing balance of power within the music industries, the role of the state in regulating and promoting various musical activities within an increasingly globalised music economy, and the effects of demographic and other social changes on music culture. Drawing on new archival research, a wide range of academic and non-academic secondary sources, participant observation and a series of interviews with key personnel, the books have the potential to become landmark works within Popular Music Studies and broader cultural history. The second volume covers the period from Hyde Park to the Hacienda (1968-84)